2014
DOI: 10.1002/ange.201307955
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Denaturation of Proteins through Aluminum‐Induced Formation of Backbone Ring Structures

Abstract: A combination of ab initio calculations, circular dichroism, nuclear magnetic resonance, and X‐ray photoelectron spectroscopy has shown that aluminum ions can induce the formation of backbone ring structures in a wide range of peptides, including neurodegenerative disease related motifs. These ring structures greatly destabilize the protein and result in irreversible denaturation. This behavior benefits from the ability of aluminum ions to form chemical bonds simultaneously with the amide nitrogen and carbonyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This incorporation can reduce the dissolution rate of the frustule, and potentially reduce the degradation rate of the frustule‐associated organic carbon (Abramson et al 2009). Second, Al can react with biomolecules in biological systems to form strong bonds and structures (Song et al 2014; Exley and Mold 2015; Mujika et al 2018), which are potentially difficult to dissociate and decompose (Zhou et al 2018 b ). As a result, Al could delay the breaking down (or lysis) of diatom cells and decrease the decomposition rate of the diatom‐produced POC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This incorporation can reduce the dissolution rate of the frustule, and potentially reduce the degradation rate of the frustule‐associated organic carbon (Abramson et al 2009). Second, Al can react with biomolecules in biological systems to form strong bonds and structures (Song et al 2014; Exley and Mold 2015; Mujika et al 2018), which are potentially difficult to dissociate and decompose (Zhou et al 2018 b ). As a result, Al could delay the breaking down (or lysis) of diatom cells and decrease the decomposition rate of the diatom‐produced POC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, once it has been internalized (Liu et al 2019), Al will bind with biomolecules (Exley and Mold 2015). The Al‐binding biomolecules would be difficult to dissociate and decompose, because Al can form strong bonds and structures with a diversity of biomolecules (Song et al 2014; Exley and Mold 2015; Mujika et al 2018). In a summary of these various factors, our recent review paper suggested that Al may play an important role in the ocean carbon cycle and climate change, by enhancing carbon fixation in the upper ocean and by facilitating carbon export and sequestration in ocean depths by reducing the decomposition and decay of organic matter (Zhou et al 2018 b ).…”
Section: Figmentioning
confidence: 99%